Simultaneous Diagnosis of Acute Crohn's Disease and Endometriosis in a Patient Affects HIV. (9th May 2018) - Casiraghi, S.; Baggi, P.; Lanza, P.; Bozzola, A.; Vinco, A.; Villanacci, V.; Castelli, F.; Ronconi, M.
Abstract : This is the case report of a 45-year-old woman affected by HIV, who was hospitalized for diffuse abdominal pain, constipation, and weight loss present for over one month. A colonoscopy showed the presence of a nontransitable stenosis of the ascending colon. A right hemicolectomy was performed. The histological examination reports CD with outbreaks of endometriosis. CD and the HIV infection may coexist in the same individual and it seems that HIV reduces the relapse rate in IBD patients. CD and intestinal endometriosis can also occur simultaneously. The diagnosis is often only made after surgical resection of the diseased segment. These patients were more likely to have stricturing CD but endometriosis does not seem to impact the natural history of CD.